P716 A 2-week course of Exclusive Enteral Nutrition followed by the Crohn Disease Exclusion Diet is effective for Induction and Maintenance of Remission in children with Crohn Disease; the DIETOMICS-CD trial. (30th January 2023) - Sigall-Boneh, R; Manuel Navas-López, V; Hussey, S; Pujol Muncunill, G; Lawrence, S; Jonsson Rolandsdotter, H; Otley, A; Martín-de-Carpi, J; Abramas, L; Herrador López, M; Egea Castillo, N; Chen, M; et al.
Abstract: Background: Exclusive enteral Nutrition (EEN) is considered a first line therapy for children with active Crohn disease (CD). CD Exclusion Diet (CDED)+Partial Enteral Nutrition (PEN) is effective for induction of remission in mild-moderate CD at weeks 6 and 12, with better tolerance than EEN. We assessed whether a 2-week course of EEN, followed by CDED+PEN is superior to 8 weeks of EEN in sustaining clinical remission at week 14, outcomes of CDED up to 24 weeks, and the utility of CDED in mild-severe CD. Methods: This international, multicenter, randomized-controlled trial compared 2 weeks of EEN (Modulen, Nestle Health Science) followed by 3 phases of the CDED+PEN to 8 weeks of EEN, followed by PEN with free diet, both up to week 24. Children aged 8-18 with CD<3 years, mild-severe disease [paediatric CD activity index (PCDAI) 15-47.5], and active inflammation [elevated C-reactive protein (CRP) or faecal calprotectin (FCP)] were included. Stable immunomodulator (IM) treatment was allowed. Naïve patients were allowed to start an IM from week 4. Results: Of the 63 eligible patients enrolled, 55 were randomized and included in the final intention to treat analysis (target recruitment failed due to COVID); Group 1 (CDED+PEN;29) and group 2 (EEN;26), mean age 12.7±2.4. Steroids-free sustained remission at week 14 was obtained in 20/29(69%) in group 1 and 16/26(61.5%) in group 2, p=0.56. Remission at week 8 was obtained in 22/29(76%) in group 1 and 14/26(54%) in group 2, p=0.08. 16/29(55%) in group 1 and 9/26(34%) in group 2 maintained clinical remission at week 24; p=0.12. Median PCDAI declined from 32.5[20-36.2] to 2.5[0-5.6] and 1.2[0-5.6] in group 1 (p<0.001 for all), and from 22.5[20-29.3] to 0[0-4.3] and 0[0-2.5] in group 2 (p<0.005 for all) at baseline, week 8 and 14 respectively. Median CRP improved in group 1 from 32 mg/L[6-69] to 5[2-16] and 3[2-10.1] (p<0.001 for both) and in group 2 from 10.35 mg/L[5-33] to 3.7[2.2-7.2], p=0.012 and 3.2[2.8-5], p=0.006 at baseline, week 8 and 14 respectively. Median FCP declined in group 1 from 1946 µg/g [862-3304] to 802[196-1312] at week 8 and 241[82-1175] at week 14 (p<0.01 for both), and in group 2 from 1615[605-2692] at baseline to 436[252-1389] at week 8, which then increased to 731[349-1305] at week 14 (p<0.01 for both). At week 14, 12/22(54%) received IM from group 1 and 15/16(93%) from group 2; p= 0.009. Conclusion: Two weeks of EEN followed by CDED&PEN and EEN were successful in induction of clinical and biochemical remission in mild-severe paediatric CD, and most CDED+PEN patients-maintained remission to 24 weeks. Sustained clinical remission at week 14 was similar despite higher IM use in the EEN Group, suggesting that CDED might prevents diet-induced inflammation regardless of IM use.